Blood Pressure Control and Cardiovascular Risk Profiles among Post-stroke Survivors: A Cross-sectional Study - Wong, Hui Jie; Harith, Sakinah; Lua, Pei Lin; Ibrahim, Khairul Azmi (IIUM Medical Journal Malaysia, 2020)
INTRODUCTION: Control of modifiable risk factors is important in recurrent stroke prevention strategies. This study aimed to determine the control of blood pressure and other cardiovascular risk profiles among poststroke patients. Factors associated with uncontrolled blood pressure were also determined. MATERIAL AND METHODS: A cross-sectional study was conducted in the outpatient clinics of three hospitals located in the East Coast region of Peninsular Malaysia from May to August 2019. Information on socio-demographic characteristics, clinical profiles, and lifestyle practices were acquired. Univariate and multivariate logistic regression analyses were carried out. Crude odds ratio and adjusted odds ratio (aOR) were reported. RESULTS: From a total of 398 stroke patients, majority of the respondents were elderly with first-ever stroke, ischaemic type, and duration of stroke less than 24 months. Uncontrolled blood pressure (52%), overweight and obesity (65%), abdominal obesity (54%), and low physical activity level (65%) were common among the patients. Patients with hypertension (aOR= 3.11, 95% CI: 1.38, 6.99), diabetes mellitus (aOR 1.57, 95% CI: 1.03, 2.38), not taking prescribed medication every day (aOR 2.28, 95% CI: 1.29, 4.01), overweight (aOR 1.75, 95% CI:1.02, 2.99), obesity (aOR 1.99, 95% CI: 1.12, 3.53), and low physical activity level (aOR 2.10, 95% CI: 1.35, 3.27) were at a higher risk of having uncontrolled blood pressure. CONCLUSION: Uncontrolled blood pressure and other major cardiovascular risk factors were highly prevalent among poststroke patients. Increased efforts must be made to optimise the risk profiles management of these high-risk patients to prevent recurrent vascular events in the future.